The Social sciences : information system (Moscow : Social Sciences Today, 1985)
The collection contains articles by Soviet scholars on the information system on social sciences, its role in raising the efficiency of scientific research.
Problems of the Contemporary World (No. 118)
rpm 22/01/2019
Loans
Keywords: Social Sciences; Information System